Relationship between electrode size and machined surface in the EDM machining process - Mohd Azrul Aminur, Ismail (2008)
Electro-Discharge Machining (EDM) has found widespread application in the fabrication of Micro-Electro Mechanical Systems (MEMS), tool and mold industries and aerospace industries. The machining technique now plays an indispensable role in the fabrication of a wide variety of components. However due to rapid heating and cooling during machining, a thermally affected layer will form on the machined surface. A close inspection reveals the presence of many surface defects such as void, cracks, shallow crater and debris on this layer. Tungsten carbide (WC) with 15% of cobalt content is selected as the workpiece material and the copper tungsten as the electrode in this experiment. The electrodes are consisting in three different sizes are 3mm, 6mm and 8mm of diameter. Since EDM has been shown to be a versatile method for machining difficult-to-work materials, it is believed that the EDM process will open up an opportunity for the machining of tungsten carbide (WC). The aim of this study is to analyzes the machined surface in term of surface roughness that influenced by the different size of electrodes. After completion the experiment process, scanning electron microscope (SEM) will be employed to analyze the surface topography and the surface roughness tester will be used to measure the surface roughness on the machined surface.